First total synthesis of mariamide A. Issue 1 (January 2020) - Xia, Yamu; Chen, Chenglong; Li, Mengying; Zhou, Weizeng; Sun, Shuyu; Chu, Shanpeng; Wang, Hui
Mariamide A, a lignanamide isolated from the seeds of Silybum marianum, has demonstrated potential utility as an antioxidant and antidiabetic agent and possesses an 8-O-4′ neolignan skeleton. Herein, a first total synthesis of mariamide A is presented that proceeds in nine steps using vanillin as the starting material. The key steps for the preparation of mariamide A involve an I2 -catalyzed bromomethoxylation of an alkene group, a nucleophilic substitution followed by a sequential elimination and a monoacylation reaction.